Ankylosing spondylitis in monozygotic twins: studies on immunological parameters. Issue 7 (1st July 1999) - Höhler, Thomas; Hug, Rosula; Schneider, Peter M; Krummenauer, Frank; Gripenberg-Lerche, Christel; Granfors, Kaisa; Märker-Hermann, Elisabeth
Abstract : OBJECTIVE: To examine immunological parameters that might explain disease discordance in monozygotic twin pairs with ankylosing spondylitis (AS). METHODS: 11 monozygotic twin pairs (nine with AS, two with undifferentiated spondyloarthropathy) were investigated. The peripheral T cell receptor Vβ repertoire was investigated using FACS analysis and 14 different Vβ antibodies. In addition serum samples were tested for antibodies to Klebsiella pneumoniae, Streptococcus pyogenes, Candida albicans, Proteus mirabilis, and Escherichia coli. Peripheral blood lymphocyte reactivity against a number of bacteria was investigated by interferon γ ELISPOT assays. RESULTS: Twins suffering from AS showed cellular hyporeactivity against K pneumoniae, S pyogenes, C albicans in the ELISPOT assays compared with healthy twins. In contrast with the antibody data, where no significant differences were observed between the two groups, AS concordant twins showed the most pronounced differences in their Vβ repertoire on CD4+ and CD8+ lymphocytes. CONCLUSIONS: Cellular hyporeactivity of peripheral blood cells to bacterial antigens might reflect defective T cell responses allowing bacterial antigens to persist in diseased patients. There are probably other environmental factors that influence disease concordance.